2013
DOI: 10.1002/pmic.201300154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the EGFR interactome reveals associated protein complex networks and intracellular receptor dynamics

Abstract: Growth factor receptor mediated signaling is meanwhile recognized as a complex signaling network, which is initiated by recruiting specific patterns of adaptor proteins to the intracellular domain of epidermal growth factor receptor (EGFR). Approaches to globally identify EGFR-binding proteins are required to elucidate this network. We affinity-purified EGFR with its interacting proteins by coprecipitation from lysates of A431 cells. A total of 183 proteins were repeatedly detected in high-resolution MS measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 58 publications
3
44
0
Order By: Relevance
“…Recently, exocyst complexes have been implicated in starvation induced autophagy (Bodemann et al, 2011). A proteomic screen demonstrated that exocyst subunits interact with the EGFR complex (Foerster et al, 2013); we therefore explored if LAPTM4B and inactive EGFR interact with exocyst complex to modulate autophagy. As shown in Figures 5A and 5B, LAPTM4B and EGFR interact with multiple subunits of the exocyst complex.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, exocyst complexes have been implicated in starvation induced autophagy (Bodemann et al, 2011). A proteomic screen demonstrated that exocyst subunits interact with the EGFR complex (Foerster et al, 2013); we therefore explored if LAPTM4B and inactive EGFR interact with exocyst complex to modulate autophagy. As shown in Figures 5A and 5B, LAPTM4B and EGFR interact with multiple subunits of the exocyst complex.…”
Section: Resultsmentioning
confidence: 99%
“…Signal transduction from the receptor at the plasma membrane to downstream MAPK components requires coordination among signaling proteins. IQGAP1 associates with several MAPK proteins, including EGFR [42, 43], K-Ras [44], Raf [45, 46], MEK [14] and ERK [13, 14] (Figure 1Ai) (Table 1), providing a scaffold which promotes EGF-induced MAPK signaling [13, 45]. IQGAP3, which interacts with H-Ras [47] and ERK1 [48], also augments EGF-stimulated MAPK signaling.…”
Section: Iqgap1 Modulates Cellular Signalingmentioning
confidence: 99%
“…The interactome of the epidermal growth factor receptor (EGFR) was identified and quantified. The newly developed Cytoscape plugin ModuleGraph facilitated the extension and functional investigation of this network [74]. A short 5-item questionnaire for routine clinical assessment of childhood abuse and neglect has been developed and validated [3,75].…”
Section: Discussionmentioning
confidence: 99%